Analysis of Prognostic Factors in Pancreatic Metastases: A Multicenter Retrospective Analysis. Issue 8 (September 2018) - Ito, Takashi; Takada, Ryoji; Omoto, Shunsuke; Tsuda, Motoyuki; Masuda, Daisuke; Kato, Hironari; Matsumoto, Toshihiko; Moriyama, Ichiro; Okabe, Yoshinobu; Shiomi, Hideyuki; Ishida, Etsuji; Hatamaru, Keiichi; et al.
Abstract : Objectives: Pancreatic metastases (PMs) account for 1% to 2% of pancreatic tumors, and their prognostic significance is poorly defined. We evaluated the incidence and clinical characteristics of primary tumors and defined prognostic factors. Methods: This retrospective study of 39 Japanese tertiary referral hospitals (January 2005 to August 2015) analyzed patient and tumor characteristics and survival time. Kaplan-Meier analysis and Cox proportional hazards models were applied to evaluate overall survival and prognostic factors, respectively. Results: We enrolled 159 patients with a pathologic diagnosis of PM. The most common primary tumor was renal cell carcinoma (38.4%), followed by lung cancer (24.5%), colorectal cancer (11.3%), and sarcoma (6.3%). Eight patients were lost during follow-up, and 151 patients were included for statistical analysis. Median overall survival was 43.0 months, and the 5-year survival rate was 42.6%. Multivariate analysis identified 3 independent prognostic factors: extrapancreatic metastasis (hazard ratio, 2.13; 95% confidence interval, 1.11–4.07; P = 0.02), tumor-related symptoms at diagnosis (hazard ratio, 5.39; 95% confidence interval, 2.92–9.91; P < 0.001), and pathologic diagnosis of primary tumors ( P < 0.001). Conclusions: Treatment strategies and prognoses for PMs completely differ according to the primary tumor type. A definitive pathologic diagnosis of PMs is essential for selecting the appropriate treatment.